Endolymphatic mass in a patient with undiagnosed multiple myeloma - Michael M McDowell; Xiao Zhu; Nitin Agarwal; Georgios A Zenonos; Paul A Gardner (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2020)
Intracranial lesions located within the region of the endolymphatic sac are typically associated with locally invasive disease rather than metastasis. In this case, we report on a 68-year-old man with no oncological history presenting with vertigo and hyperacusis, who was found to have a solitary enhancing mass of the left temporal bone. Subsequent systemic imaging raised concern for a metastatic lesion, and the patient was ultimately diagnosed with multiple myeloma. Multiple myeloma rarely presents with symptomatology consistent with intracranial pathology. This report highlights the importance of surveillance for metastatic disease even when primary lesions are suspected.